Determinants of Value Chain Analysis of Solar Photovoltaic Industry in Kathmandu Valley - Rizal, Anita (Journal of Business and Social Sciences Research, 2018)
The objective of this paper is to find out key factors influencing target market of solar photovoltaic industry; and identify ways on how to reduce cost of sales in solar photovoltaic industry in Nepal. It also analyzes better ways of marketing solar photovoltaic system in current market. The conceptual model taken for this study comprises of Porter’s (1985) value chain analysis theory which has identified two sequences of activities i.e. primary and support activities. Exploratory research has been used where primary data is collected through structured questionnaire distributed among 120 individual sellers of solar photovoltaic system inside Kathmandu valley. The data collected are analyzed using SPSS 16.0 which is coded and tabulated by Microsoft Excel spreadsheet application.The result of the analysis of the data shows that factors influencing value chain of solar PV industry are infrastructure (mostly furniture, workshop, showroom, capital and human resources in less number) needed to set up a company, imported from different countries, distribution channel, subsidy claim, marketing medium and after sales service. Few companies import huge quantity of solar related products. Most of the companies targeting direct customer don't claim subsidy directly rather they claim via other pre-qualified companies. Also these companies consider radio advertisement to reach customers at large rather than any other medium of marketing. These companies value warranty and repair & maintenance services as an after sales service. Although few of the solar photovoltaic systems are manufactured in Nepal, they prefer to import these items rather than promote Nepal made products. Thus, these factors have created value from import to service to the customers.Journal of Business and Social Sciences Research, Vol. 1, No. 2, pp. 153-168